Efficiency and resource allocation: the Hungarian managed health care system - Jóna, György (Competitio, 2011)
The managed health care system (MHCS) was introduced and applied in Hungary between 1999 and 2009. The gradually expanding system covered only 22% of the population and included exclusively the curative-preventive health care, subsidy on medicaments, subsidy on therapeutic appliances and the spa service. Like anywhere else it was cost-effectiveness that was expected from the MHCS without the adverse effect in the quality of the health service. To decide whether the MHCS was successful in Hungary or not, we compare it with the results of those segments of the health system where the MHCS was not introduced. We use the method of the incremental cost analysis. We are making our comparison exclusively on the basis of health economics aspects, because no difference has evolved in the quality of the medical attendances. We will see that where the MHCS was applied, the medical attendance became cheaper, at those places where the MHCS was not applied the medical attendance became more expensive, causing a chronic financial deficit (137785 million HUF). Although the MHCS managed from less money, it gained 17767 million HUF during the mentioned ten years. We are going to present the general features of the MHCS and support the fact that the outcome of the managed care concept was rationalized and the savings in several segments of health care, by means of empirical evidence.Journal of Economic Literature (JEL) classification: I150, I180, G220, G320, H520.